Кон Jere Paul Surber, Culture and Critique: An Introduction to the Critical Discourses of Cultural Studies: Për Jere Paul Surber, Culture and Critique: An Introduction to the Critical Discourses of Cultural Studies - Stamatov, Aleksandar; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2005)
Author(s): Aleksandar Stamatov | Александар Стаматов Title (Macedonian): Кон Jere Paul Surber, Culture and Critique: An Introduction to the Critical Discourses of Cultural Studies Title (Albanian): Për Jere Paul Surber, Culture and Critique: An Introduction to the Critical Discourses of Cultural Studies Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005 Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 367-369 Page Count: 3 Citation (Macedonian): Александар Стаматов, „Кон Jere Paul Surber, Culture and Critique: An Introduction to the Critical Discourses of Cultural Studies“, Идентитети: списание за политика, род и култура, т. 4, бр. 1-2 (лето - зима 2005): Citation (Albanian): Aleksandar Stamatov, „Për Jere Paul Surber, Culture and Critique: An Introduction to the Critical Discourses of Cultural Studies“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005): 367-369.